GABA induction of the Saccharomyces cerevisiae UGA4 gene depends on the quality of the carbon source: Role of the key transcription factors acting in this process - Levi, Carolina E. (2012)
Yeast cells are able to adapt their metabolism according to the quality of both carbon and nitrogen sources available in the environment. Saccharomyces cerevisiae UGA4 gene encodes a permease capable of transporting γ-aminobutyric acid (GABA) into the cells. Yeast uses this amino acid as a nitrogen source or as a carbon skeleton that enters the tricarboxylic acid cycle.The quality of the carbon source modulates UGA4 expression through two parallel pathways, each one acting on different regulatory elements, the UASGATA and the UASGABA. In the presence of a fermentable carbon source, UGA4 expression is induced by GABA while in the presence of a non-fermentable carbon source this expression is GABA-independent.The aim of this work was to study the mechanisms responsible for the differences in the profiles of UGA4 expression in both growth conditions.We found that although the subcellular localization of Gln3 depends on the carbon source and UGA4 expression depends on Tor1 and Snf1, Gln3 localization does not depend on these kinases. We also found that the phosphorylation of Gln3 is mediated by two systems activated by a non-fermentable carbon source, involving the Snf1 kinase and an unidentified TORC1-regulated kinase.We also found that the activity of the main transcription factors responsible for UGA4 induction by GABA varies depending on the quality of the carbon source. In a fermentable carbon source such as glucose, the negative GATA factor Dal80 binds to UGA4 promoter; only after the addition of the inducer, the positive factors Uga3, Dal81 and Gln3 interact with the promoter removing Dal80 and leading to gene induction. In contrast, in the non-fermentable carbon source acetate the negative GATA factor remains bound to UGA4 promoter in the presence or absence of GABA, the positive factors are not detected bound in any of these conditions and in consequence, UGA4 is not induced.